Accessing the Impacts of Contemporary Development in Biofuel on Agriculture, Energy and Domestic Economy: Evidence from Nigeria - Olanrele, Iyabo Adeola; Lawal, Adedoyin I.; Oseni, Ezekiel; Adekunle, Ahmed Oluwatobi; Lawal-Adedoyin, Bukola, B.; Elleke, Crystal O.; Ojeka-John, Racheal; Nweke-Love, Henry (International Journal of Energy Economics and Policy, 2020)
The recent volatility of the conventional energy output owning to fluctuations in the supply chain in the fossil fuel cum with its finite supply nature has necessitate the integration of biofuel into the global energy needs. Biofuel as a type of renewable energy has the ability to reduce global warming resulting from greenhouse gas (GHG) emissions, thus offers a relatively healthy energy option for both the consumers and producers in global space. This notwithstanding has some implications on agriculture and food security. This paper examined the impact of biofuels development on agriculture, energy infrastructure and domestic wellbeing in Nigeria. The study identified a potential rivalrous relationship in terms of space and cultivation mechanism when sustainability is in view. We reviewed existing policies and sustainability practices in other economies and concludes that Nigeria needs a deliberate effort aimed at developing institutional structures that will facilitate building and expansion of the biofuels sub-sector at the same time enhance rural livelihood. Keywords: Biofuel, agriculture, energy, wellbeing, Nigeria JEL Classifications: E22; G13; G22 DOI: https://doi.org/10.32479/ijeep.10169